2021
DOI: 10.1097/jhm-d-20-00283
|View full text |Cite
|
Sign up to set email alerts
|

Value-Based Healthcare Initiatives in Practice: A Systematic Review

Abstract: EXECUTIVE SUMMARY Value-based initiatives are growing in importance as strategic models of healthcare management, prompting the need for an in-depth exploration of their outcome measures. This systematic review aimed to identify measures that are being used in the application of the value agenda. Multiple electronic databases (PubMed/MEDLINE, Embase, Scopus, Cochrane Central Register of Controlled Trials) were searched. Eligible studies reported various implementations of value-based healthcare init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 58 publications
(94 reference statements)
1
31
0
Order By: Relevance
“…In view of the recent advancements in spine treatments, surgery is considered clinically effective from a medical perspective. However, healthcare systems are progressively moving toward value-based business models ( 2 ), with the definition of clinical success increasingly based on patient-reported outcome measures (PROMs) ( 3 ). The Oswestry disability index (ODI) is a widely-used, validated, and self-administered questionnaire to assess a patient's functional impairment related to the spinal condition, encompassing questions about personal care, movements, sleeping, and social life ( 4 ), and can be used to evaluate the outcomes from the patient's perspective ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the recent advancements in spine treatments, surgery is considered clinically effective from a medical perspective. However, healthcare systems are progressively moving toward value-based business models ( 2 ), with the definition of clinical success increasingly based on patient-reported outcome measures (PROMs) ( 3 ). The Oswestry disability index (ODI) is a widely-used, validated, and self-administered questionnaire to assess a patient's functional impairment related to the spinal condition, encompassing questions about personal care, movements, sleeping, and social life ( 4 ), and can be used to evaluate the outcomes from the patient's perspective ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although superficially attractive, much depends on how value-based healthcare is defined. Of concern is the possibility that PHI-payors will use a narrow interpretation of value-based healthcare as a way to reduce costs through inducements and financial penalties rather than one that encompasses healthcare outcomes that are important to patients and carers (Zanotto et al, 2021). We discuss the implications of a narrow PHI-payor-driven implementation of value-based healthcare, based primarily on cost reduction, for private psychiatric practice in Australia.…”
mentioning
confidence: 99%
“…The evidence to date is not encouraging, with limited data on outcome measures that are relevant to mental health patients. More broadly, a systematic qualitative review of the outcome research on value-based healthcare in general found that of 47 included studies, only 16 used patient-reported outcome measures, and only 3 reported comprehensive outcomes (Zanotto et al, 2021). This was less than those specifically reporting cost-saving outcomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations